(untitled) (Damascus University Journal for legal sciences, 2025)
The study dealt with share transfer plans considering it an incentive reward Islamic Financial Institutions use to motivate their employees and senior executives. Through this study, the researcher tries to explain the methods followed in motivation through shares, the sources of providing them, and their Islamic ruling. The study showed that the share transfer incentive can be through share options, restricted share purchase plans, or free grants of restricted shares. Shares are made available through an increase in capital by private offering, or through treasury shares where ownership is transferred to employees. The study concluded that incentive methods are permissible, and explained the Islamic ruling on the issues related to it, and the permissible ways used by institutions in order to provide shares. The researcher also suggested an alternative method for share options based on granting a special discount on conditions determined by the institution for employees wishing to own shares.